2021
DOI: 10.1038/s41467-021-26803-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 B.1.1.7 (alpha) and B.1.351 (beta) variants induce pathogenic patterns in K18-hACE2 transgenic mice distinct from early strains

Abstract: SARS-CoV-2 variants of concern (VOC) B.1.1.7 (alpha) and B.1.351 (beta) show increased transmissibility and enhanced antibody neutralization resistance. Here we demonstrate in K18-hACE2 transgenic mice that B.1.1.7 and B.1.351 are 100-fold more lethal than the original SARS-CoV-2 bearing 614D. B.1.1.7 and B.1.351 cause more severe organ lesions in K18-hACE2 mice than early SARS-CoV-2 strains bearing 614D or 614G, with B.1.1.7 and B.1.351 infection resulting in distinct tissue-specific cytokine signatures, sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 60 publications
6
81
0
Order By: Relevance
“…However, other recent studies have shown that intranasal infection of K18-hACE2 mice with B.1.1.7 and B.1.351 variants resulted in distinct arrays of cytokine response than those induced by early SARS-CoV-2 strains. Several myeloid cell chemoattractants showed enhanced pulmonary secretions in K18-hACE2 mice following exposures to B.1.1.7 or B.1.351 variant [29,30]. These findings are consistent with previous studies in humans, which established a consistent link between the mutations exhibited by the B.1.351 lineage and a greater potential for infectivity and immune escape [4,6,24].…”
Section: Discussionsupporting
confidence: 89%
“…However, other recent studies have shown that intranasal infection of K18-hACE2 mice with B.1.1.7 and B.1.351 variants resulted in distinct arrays of cytokine response than those induced by early SARS-CoV-2 strains. Several myeloid cell chemoattractants showed enhanced pulmonary secretions in K18-hACE2 mice following exposures to B.1.1.7 or B.1.351 variant [29,30]. These findings are consistent with previous studies in humans, which established a consistent link between the mutations exhibited by the B.1.351 lineage and a greater potential for infectivity and immune escape [4,6,24].…”
Section: Discussionsupporting
confidence: 89%
“…The B.1.351 variant, originally identified in South Africa, includes several mutations within the structural and nonstructural proteins raising significant concerns about alterations to viral fitness, transmission, and disease 44 . SARS-CoV-2 variants B.1.1.7 (alpha) and B.1.351 45 are reported to have increased transmission and resistance to antibody neutralization 46 . The SARS-CoV-2 Omicron variant B.1.1.529 harbors more than 30 changes to the spike protein and has an increased risk of reinfection compared to other VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…org/sars-cov-2/). In K18-hACE2 transgenic mice, alpha and beta VOCs induced pathogenic patterns and were 100-fold more lethal than early SARS-CoV-2 lineages (115). The European Centre for Disease Prevention and Control (ECDC), compared the COVID-19 severity cases between VOCs and non-VOCs, and observed that the beta variant was associated with a higher ratio for hospitalization (3.6) (60).…”
Section: Emerging Sars-cov-2 Variants Of Concernmentioning
confidence: 99%